Tradisi Manggadaikan Anak Ka Bako setelah Masa Penyusuan Perspektif Maslahah di Kelurahan Balai Panjang, Kecamatan Payakumbuh Selatan, Kota Payakumbuh - Azzahra Dwi Puteri; Dahyul Daipon (AHKAM, 2026)
Although the tradition of manggadaikan anak ka bako following the breastfeeding period remains recognized by some Minangkabau communities, studies specifically examining its practice, meaning, and status from the perspective of maslahah remain limited. This study aimed to identify the practice and meaning of the manggadaikan anak ka bako tradition following the breastfeeding period in Balai Panjang Urban Village, South Payakumbuh Subdistrict, Payakumbuh City, and to analyze its status from the perspectives of customary law and Islamic law through a maslahah approach. This study employed a qualitative approach with a descriptive field research design. Data were collected through interviews, observation, and documentation involving parents, bako families, customary leaders, and community members familiar with the practice and were subsequently analyzed descriptively and inductively. The findings showed that this tradition was performed through the symbolic handover of a child to the bako family following the breastfeeding period. The term “pledge” in this tradition does not indicate the transfer of custody, responsibility, or the child’s legal status because caregiving remains with the biological parents. This tradition is understood as an effort to safeguard the child’s health and well-being while strengthening kinship relations. From the perspective of maslahah, the manggadaikan anak ka bako tradition may be conditionally maintained provided that it causes no harm, does not deprive children of their rights, and does not conflict with the principles of Islamic law. This study concludes that the tradition functions as a symbolic practice and a social mechanism of kinship rather than as a transfer of caregiving responsibility. These findings broaden scholarship on the relationship among Minangkabau customs, bako kinship, child protection, and maslahah in Islamic family law.